Anxiety sensitivity as predictor of pain in patients undergoing restorative dental procedures - Klages U, Kianifard S, Ulusoy O¨ , Wehrbein H (Blackwell Synergy, 2006)
The personality disposition to anxiety sensitivity refers to beliefs about negative consequences of bodily arousal.